A Glance at the Developmental Opportunities of Gibe III Hydro Electric Power Project of Ethiopia at National Level Vis-A-Vis Local Communities (Global Journal of Human-Social Science, 2018)
With a great deal of enthusiasm to make a way out of extreme poverty the government of Ethiopia is claiming the fact that it was embarked on a track of developmental ventures that would bring economic transformation for the nation To this end priorities were given to the power sector which is believed to be serving as foundation for the upcoming shift from agrarian economy to the manufacturing industry in short period of time as was envisaged by the Growth and Transformation Plan of the incumbent gov t Accordingly massive investments are on the stake in power generation projects particularly in the hydroelectric sector One of such endeavours is the Gibe III hydroelectric power project which is launched in 2006 The purpose of this short article is to observe the balance of national development initiative with the concern of local communities adjacent to the project centre Accordingly the government is keen explaining the projects role in boosting the nation s energy supply in the field of electric city and above all it opens the way for earning foreign currency since part of the energy produced is going to be exported to the neighbouring states including Kenya With regard to localities of the project area based on the information directly obtained from informants representing the communities there are some developmental opportunities associated with the project which includes infrastructure social services alternatives labour intensive economic activities support in some aspects of agricultural modernization providing productive crops species Etc
Keywords: development; local communities